Predicting the Intention to Purchase Electric Vehicles in South Africa - FATOKI, Olawale (Journal of Environmental Management and Tourism, 2021)
One of the major contributors to the relatively high levels of Greenhouse gas emissions in South Africa is road transportation. Electric vehicles (EVs) have been proposed as one of the solutions to this problem. However, the use of EVs is very limited in South Africa. Drawing on the Theory of Planned Behaviour (TPB), the study investigated the predictors of the intention to purchase EVs in South Africa. The study extended the TPB by adding three individual constructs (environmental consciousness, anticipated guilt and response efficacy) and two situational constructs (perceived benefits and perceived barriers). The cross-sectional survey method was used for data collection in a quantitative study. Descriptive statistics and structural equation modelling were used for data analysis. The results showed significant positive relationships between two TPB constructs (attitude and perceived behavioral control) and EV purchase intention. In addition, the effects of the environmental consciousness, response efficacy, perceived benefits and barriers are significant. Theoretically, the study extended the TPB to develop a model of EV purchase intention from the South African perspective. Empirically, the study added to the body of literature on the determinants of EV purchase intention. Practically, recommendations to improve the purchase of EVs are suggested.